Pengaruh Model Pembelajaran terhadap Hasil Belajar Siswa SMK Otomotif: Meta Analisis - Fatah, Amirrudin; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to analyze the effectiveness of various learning models on the learning outcomes of Automotive Vocational High School students through a quantitative meta-analysis approach. Secondary data were obtained from Google Scholar and Garuda using keywords such as